Ultimate bearing capacities of large diameter pipeline elbows with ellipsoidal pits. (January 2021) - Li, Yuan; Qin, Guoliang; Wang, Xinyi; Zhang, Yazhao; Zhang, Zhihao
Highlights: The material is API X80 steel and the curvature radius is 6 D. The plastic failure criterion and twice elastic slope method were adopted to determine the limit internal pressure load. Using the commercial finite element software, Abaqus, the influences of defect location, defect depth, defect length, defect width and pipe wall thickness on the ultimate bearing capacity of an pipe elbow with ellipsoidal pits was studied. Through multiple nonlinear regression analysis and nonlinear fitting, formulas for calculating the ultimate internal pressure load of large-diameter elbows with defects under various influencing factors were obtained. The formulas can provide guidance and reference for evaluating the residual strength of large-diameter elbows with defects. Abstract: Defects significantly affect the carrying capacity of pipe elbows. Accurately estimating the capacity permits fewer pipe inspections and replacements, saving time and reducing costs. To study the effect of defects, a 90° pipe elbow model with a 1016 mm-diameter and 19.9 mm wall thickness was built. The material is API X80 steel and the curvature radius is 6D. The plastic failure criterion and twice elastic slope method were adopted to determine the limit internal pressure load. Using the commercial finite element software, Abaqus, the influences of defect location, defect depth, defect length, defect width and pipe wall thickness on the ultimate bearing capacity of an pipe elbow with ellipsoidal pits was studied. Through multiple nonlinear regression analysis and nonlinear fitting, formulas for calculating the ultimate internal pressure load of large-diameter elbows with defects under various influencing factors were obtained. The formulas can provide guidance and reference for evaluating the residual strength of large-diameter elbows with defects.